Relationship between surface roughness and stability of standard weight - Intiang, Jittakant (Bulletin of Applied Sciences, 2022)
In this research, the relationship between surface roughness and stability of standard weight with different surface roughness i.e. 0.02636, 0.15315, 0.48183, 0.87301 and 1.04617 µm was studied. The study was conducted by obtaining the change of mass value versus time scale in one year. The results are shown that mass value of the standard weight will be increasing 0.99, 1.28, 1.42, 1.97 and 2.23 mg respectively per year. It can conclude that the standard weight with more surface roughness value will show more increasing in mass value.